2010
DOI: 10.1073/pnas.1006432107
|View full text |Cite
|
Sign up to set email alerts
|

Conserved vertebrate mir-451 provides a platform for Dicer-independent, Ago2-mediated microRNA biogenesis

Abstract: Canonical animal microRNAs (miRNAs) are generated by sequential cleavage of precursor substrates by the Drosha and Dicer RNase III enzymes. Several variant pathways exploit other RNA metabolic activities to generate functional miRNAs. However, all of these pathways culminate in Dicer cleavage, suggesting that this is a unifying feature of miRNA biogenesis. Here, we show that maturation of miR-451, a functional miRNA that is perfectly conserved among vertebrates, is independent of Dicer. Instead, structure-func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
417
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 422 publications
(438 citation statements)
references
References 44 publications
(46 reference statements)
18
417
0
3
Order By: Relevance
“…1C). Interestingly, Cifuentes and colleagues observed that Ago2 protected the approximately 30-nt slicercleaved intermediate from RNase I in vitro, resulting in a approximately 20-to 26-nt 3 0 -end trimmed product, similar to the observations by Yang and colleagues (5,7,31,32). Recently, Yang and colleagues show that the degree of G:C content in the resected region governs the maturation efficiency of 3 0 resection and resultant regulatory activity, such that a relatively low G:C content improves processing (31).…”
Section: Mechanisms Of Mir-451 Biogenesissupporting
confidence: 65%
See 2 more Smart Citations
“…1C). Interestingly, Cifuentes and colleagues observed that Ago2 protected the approximately 30-nt slicercleaved intermediate from RNase I in vitro, resulting in a approximately 20-to 26-nt 3 0 -end trimmed product, similar to the observations by Yang and colleagues (5,7,31,32). Recently, Yang and colleagues show that the degree of G:C content in the resected region governs the maturation efficiency of 3 0 resection and resultant regulatory activity, such that a relatively low G:C content improves processing (31).…”
Section: Mechanisms Of Mir-451 Biogenesissupporting
confidence: 65%
“…The 42-nt Drosha-cleaved miR-451 hairpin with a 17-nt stem does not possess a sufficiently long duplex to be a Dicer substrate (>19 nt), suggesting that its maturation might bypass a requirement for Dicer (27). Recently, 3 studies found by coincidence that the maturation of miR-451 seemed refractory to loss-of-function mutations in Dicer (5,7,10). miR-451 accumulated effectively in embryonic stem cells carrying a conditional knockout of Dicer (10), in mouse embryonic fibroblasts (MEF) stably deleted for Dicer (5) and in MZdicer mutant zebrafish (7).…”
Section: Mechanisms Of Mir-451 Biogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…For miR-451, oligouridylation at the 3 ′ end and subsequent 3 ′ trimming occurs to reach the mature miRNA length Cifuentes et al 2010;Yang et al 2010), and the poly(A)-specific endonuclease PARN was recently implicated (Yoda et al 2013). Surprisingly, trimming was found not to be essential for subsequent target mRNA silencing in vitro and in vivo (Yoda et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a growing body of evidence for the existence of noncanonical or alternative processing routes for natural miRNAs and manmade shRNAs. Whereas Dicer is critical for activation of the majority of these miRNA and shRNA molecules, notable exceptions were reported for a special set of miRNAs Cifuentes et al 2010;Miyoshi et al 2010;Yang et al 2010;Yang and Lai 2011;Havens et al 2012). More recently, Dicer-independent shRNAs have been described as well (Ge et al 2010;Dallas et al 2012;Liu et al 2013).…”
Section: Introductionmentioning
confidence: 99%